On Translation Studies in Romania - PETRARU, Ana‐Magdalena (Presa Universitară Clujeană, 2022)
This book is the result of our research conducted in the field of Translation Studies since our undergraduate years at the Faculty of Letters where we majored in English and minored in French between 2001-2005. Our bachelor thesis title was The Translator’s Notes, hence a subchaper devoted to the topic. Special thanks, in this regard, are owed to professor Rodica Dimitriu, former Head of the English Department at Alexandru Ioan Cuza University of Iași for her guidance throughout our entire academic formation (undergraduate and postgraduate years) as coordinator of our Bachelor, MA and doctoral theses. We devoted our MA dissertation to the translation of comics and, consequently, we included a subchapter on it in our study, focusing on some Romanian and English versions of Herge’s Tin Tin that we have also dealt with in the past. Last but not least, during our postdoctoral fellowship (2014-2015) we studied the Romanian discourse on translation, so most of this book is a collection of revised papers that came out then or in the following years.